Chlorinated plastoquinone analogs that inhibitStaphylococcus epidermidisandCandida albicansgrowth - Kara, Emel Mataraci; Bayrak, Nilufer; Yildirim, Hatice; Yildiz, Mahmut; Celik, Berna Ozbek; Tuyun, Amac Fatih (Springer, 2020)
Infectious diseases are the significant global health problem because of drug resistance to most classes of antimicrobials. Interest is growing in the development of new antimicrobials in pharmaceutical discovery. For that reason, the urgency for scientists to find and/or develop new important molecules is needed. Many natural active molecules that exhibit various biological activities have been isolated from the nature. For the present research, a new selected set of aminobenzoquinones, denoted as plastoquinone analogs (PQ1-24), was employed for their in vitro antimicrobial potential in a panel of seven bacterial strains (three Gram-positive and four Gram-negative bacteria) and three fungi. The results revealed PQ analogs with specific activity against bacteria includingStaphylococcus epidermidisand pathogenic fungi, includingCandida albicans.PQ8containing methoxy group at the ortho position on the phenylamino moiety exhibited the highest growth inhibition againstS. epidermidiswith a minimum inhibitory concentration of 9.76 mu g/mL. The antifungal profile of all PQ analogs indicated that five analogs (whilePQ1,PQ8,PQ9,PQ11, andPQ18were effective againstCandida albicans, PQ1andPQ18were effective againstCandida tropicalis) have potent antifungal activity. Selected analogs,PQ1andPQ18, were studied for biofilm evaluation and time-kill kinetic study for better understanding.
Keywords: Quinone analogs; Antibacterial activity; Antifungal activity; Antibiofilm activity; Natural product; Candida albicans; Staphylococcus epidermidis; Bactericidal effect